2018
DOI: 10.1007/s11673-018-9871-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient Representation and Advocacy for Alzheimer Disease in Germany and Israel

Abstract: This paper analyses self-declared aims and representation of dementia patient organizations and advocacy groups (POs) in relation to two recent upheavals: the critique of social stigmatization and biomedical research focusing on prediction. Based on twenty-six semi-structured interviews conducted in 2016–2017 with members, service recipients, and board representatives of POs in Germany and Israel, a comparative analysis was conducted, based on a grounded theory approach, to detect emerging topics within and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Alternatively, it might be associated with the low tendency to change that characterizes cultures with high levels of uncertainty avoidance (de Mooji & Hofstede, 2010). Indeed, a recent study comparing German and Israeli dementia advocacy groups, showed that German groups are more heterogeneous, allowing for self-advocacy, while Israeli groups are more traditional focusing strongly on caregivers (Schicktanz et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Alternatively, it might be associated with the low tendency to change that characterizes cultures with high levels of uncertainty avoidance (de Mooji & Hofstede, 2010). Indeed, a recent study comparing German and Israeli dementia advocacy groups, showed that German groups are more heterogeneous, allowing for self-advocacy, while Israeli groups are more traditional focusing strongly on caregivers (Schicktanz et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Advocacy may be either "for" or "of" people with dementia (Schicktanz, Rimon-Zarfaty, Raz, & Jongsma, 2018) and self-advocacy by people with dementia is a relatively recent phenomenon (Bartlett, 2012). Historically, dementia advocacy has been carer-led Schicktanz et al, 2018) and reliant on proxy views, partly due to perceived incompetence in people with dementia (Beard, 2004). UK advocacy organisation, Alzheimer's Society, was initially carer-led, innovatively involving people with dementia in governance from the early 2000s (Moreira, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By this, we do not cover the whole spectrum of POs existing within these countries. As former studies indicate, some smaller POs have stronger inclusion policies for persons with dementia than these three (Schicktanz et al, 2018). Future course of research could empirically investigate a spectrum of AD POs spread across two or more countries, holding comparative relevance in terms of having similar socio-cultural and economic infrastructure but differing or similar healthcare regimes.…”
Section: Resultsmentioning
confidence: 96%
“…By promoting inclusionary practices in the designing of the healthcare benefits (e.g., by joining national health committees or giving advice to politicians) POs enable people, especially the vulnerable ones to exercise the terms of their citizenship (Barnes and Brannelly, 2008 ). Although the AD movement was initiated by, and originally intended for the carers rather than the people with AD (Beard, 2004 ), many AD POs at present publicly identify themselves as carers' and patients' organizations, reflecting a process of hybridization of their claims and recognition of those affected (O'Donovan et al, 2013 ; Schicktanz et al, 2018 ). Due to this hybridity of representation and questioning of political citizenships of people with AD (Bartlett and O'Connor, 2007 ), it is important to recognize and reflect on the factors informing the arenas of citizenships that POs create for both people with AD and their carers.…”
Section: Introductionmentioning
confidence: 99%